Evaluation of Digestible Lysine Needs for Male Broiler - Abudabos, A.; Aljumaah, R. (International Journal of Poultry Science, 2010)
This study was performed to evaluate the effect of feeding digestible lysine (Dig. Lys) levels in excess of NRC (1994) requirements in standard corn-soy rations from one to 42 d of age. A total of 960 one d old (Cobb 500) chicks were obtained from a commercial hatchery and randomly distributed in a randomized complete block design among 16 floor pens with four replicate pens/treatment. Diets were formulated to provide a minimum of 100% of NRC recommendation levels of amino acids other than Lys. Diets were fortified with L-lysine HCL to provide four levels of Lys (T1 = 100, T2 = 110, T3 = 120 and T4 = 130% of NRC recommendation). Birds received starter diet from 1-10 d, grower diet from 11-21 d and finisher diet from 22-42 d of age. Four pens of 60 male birds were fed one of the four experimental diets. There was a hierarchy of Lys requirements: the requirement for maximum gain was achieved when feeding T2 or T3, the requirement to maximize Breast Meat (BM) yield or Feed Conversion Ratio (FCR) was achieved when feeding T3; lastly, the requirement for percentage of minimum Abdominal Fat (AF) was achieved when feeding T4. Body weight, FCR and BM yield in birds responded quadratically while AF responded linearly to incremental Dig Lys levels. Thus, Lys requirement may be increased according to whatever criteria are desired.